The Impact of Multi-Stakeholder Partnerships on Educational Outcomes: A Case of East Africa - Wango, Nyagwegwe C.; Oluga, Mary; Rarieya, Jane F. A. (Journal of Education and Practice, 2025)
Purpose: Partnerships among educational development stakeholders have yielded long-term and mutual benefits for all participants involved, depending on the nature of their participation and contribution. Through the Foundation for learning project, the Aga Khan University's Institute for Educational Development, East Africa aims to improve learning outcomes in specific regions of Kenya, Uganda, and Tanzania. By focusing on four teacher colleges in the three countries, the Institute aimed to investigate the collaboration and role of educational and development partners, including Ministries of Education and Aga Khan Development Network (AKDN) agencies, in implementing the F4L Project. It explores how collaboration within this partnership informs educational practice and theory. Methodology: A qualitative study involving continuous observations on the outcomes of participation and contributions of the various partners was made. Findings: Findings from various stakeholders highlight the benefits of the multi partnerships, including capacity building, resource, and expertise sharing, in ultimately enhancing sustainability and the quality of education for all children. Unique contribution to theory, practice and policy (recommendations): The study shows the value add of engaging in lobbying and advocacy efforts, as well as of shared knowledge which strengthens project planning and minimizes implementation risks. The paper discusses the potential of multi-stakeholder partnerships in improving teacher education and educational outcomes in East Africa through collaboration.